2000
DOI: 10.1034/j.1399-3003.2000.16d18.x
|View full text |Cite
|
Sign up to set email alerts
|

Can peak expiratory flow be measured accuratelyduring a forced vital capacity manoeuvre?

Abstract: Can peak expiratory flow be measured accurately during a forced vital capacity manoeuvre? D. Wensley, D. Pickering, M. Silverman. #ERS Journals Ltd 2000. ABSTRACT: Spirometry and peak flow measurements traditionally depend on different forced expiratory manoeuvres and have usually been performed on separate, dedicated equipment. As spirometry becomes more widely used in primary care settings, the authors wished to determine whether there was a systematic difference between peak expiratory flow (PEF) derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
2
11
1
Order By: Relevance
“…One study compared both techniques using a turbine spirometer in two groups of children (1). In 42 children without asthma and 38 children with asthma, there was a mean 3% decrease in peak flow using the spirometric technique compared with the peak flow technique (1). Another study looked at peak flow values in 36 adult patients using the same Wright peak flow meter and either the spirometric technique or the peak flow technique (2).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…One study compared both techniques using a turbine spirometer in two groups of children (1). In 42 children without asthma and 38 children with asthma, there was a mean 3% decrease in peak flow using the spirometric technique compared with the peak flow technique (1). Another study looked at peak flow values in 36 adult patients using the same Wright peak flow meter and either the spirometric technique or the peak flow technique (2).…”
Section: Introductionmentioning
confidence: 97%
“…However, this latter or spirometric technique may result in slightly lower peak flows (1,2). One study compared both techniques using a turbine spirometer in two groups of children (1). In 42 children without asthma and 38 children with asthma, there was a mean 3% decrease in peak flow using the spirometric technique compared with the peak flow technique (1).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, we assessed PEF derived from an FVC maneuver, as did Casale et al (21) In contrast, McCarley et al (20) assessed PEF using a peak flow meter. However, two previous studies (22,23) demonstrated that the difference between the two methods for measuring PEF (i.e., with a spirometer or a peak flow meter) is small and clinically insignificant. In a previous study, Teramoto et al (24) evaluated variations in spirometric parameters in COPD patients over a 12-h period.…”
Section: Resultsmentioning
confidence: 99%